MAKAN BERGIZI GRATIS DALAM PERSPEKTIF HADIS (Kajian Ma’anil Hadis) - Ach Jalaluddin Ar Rumi; Himmatul Udzma (Al-Hasyimi: Jurnal Ilmu Hadis, 2025)
This article discusses free nutritious meals (MBG), one of the priority programs of President Prabowo Subianto and Vice President Gibran Rakabuming Raka. This program will occur during the Red and White Cabinet government starting in January 2025. Communities who are priority recipients of free nutritious meals namely pregnant women, breastfeeding mothers, as well as toddlers, and all school children in Indonesia, How does the hadith view this free nutritious meal program in from the perspective of ma'anil hadith studies. This research uses a qualitative approach with the type of literature study. This research aims to provide a comprehensive understanding of government policy by using hadith as an analytical tool in terms of hadith content as well as textual and contextual meaning. Based on the analysis of the hadith narrated by Imam Thabrani and Ali bin Abi Talib, it shows that the conclusions of this research provide us with an understanding that the free nutritious meal policy is an action that was highly recommended by the Prophet Muhammad SAW to create a superior generation for the Indonesian nation.